A mobile app for supermarket checkout - Siew, Shun Yao (2022)
Existing supermarket’s self-service technology requires a high cost when come to installing a self-service machine together with maintaining cost in the future. Besides, checkout manually at cashier counter in supermarket has resulted time consuming especially during the peak hour and vacation day. This led to overall of time operation consuming has caused stressful and contradiction due to be productivity which can provide the best service to consumer’s need. Therefore, the goal of proposed project aims to examine and investigate the situation’s underlying causes to offer a remedy. The proposed system that involved ionic framework to build web application for supermarket merchant and mobile application to checkout items themselves. Angular js is used to build the frontend component while backend server has involved AWS EC2 server to be API endpoints to communicate with frontend client and store data into PostgreSQL database. Furthermore, iteration and incremental model methodology was practiced throughout the project life cycle to achieve manage project timeline and follow up the system progress. In addition, the proposed project involved various of testing such as unit testing, integration testing and UAT testing, and all testing cases is accepted and passed. The proposed system reduced the queuing time and operation time of scanning item by cashier worker when mobile application provides self-service of scanning items and checkout through online especially consumer with less items.